Nutrition advice provided by general practice registrars: an investigation using patient scenarios. (November 2016) - Crowley, J.; Ball, L.; Wall, C.
Abstract: Background: Nutrition is recognized as a strong factor influencing the health outcomes of patients with chronic disease. General practitioners (GPs) require nutrition knowledge and skills to support patients to have healthy dietary behaviours. Objective: To investigate New Zealand GP registrars' provision of nutrition advice using patient scenarios. Study design: A cross-sectional study design targeted GP registrars to investigate the nutrition care they provided to patients. Methods: Fourty-seven GP registrars completed a survey at a training event. The survey included patient scenarios. Respondents were asked to provide nutrition advice for each scenario, in line with best practice guidelines. Responses to each scenario were scored based on a panel of nutrition experts. Regression analysis was used to compare the scores to participants' previously reported confidence to provide nutrition care. Results: Seventeen male (36.2%) and thirty female (63.8%) GP registrars completed the survey, giving a response rate of 92.2%. GP registrars scored a mean of 7.9 ± 0.2 out of 15 for recall of dietary strategies with the scenarios. There was no association between GP registrars' scenario scores and their confidence to provide nutrition care. Conclusions: An evidence-practice gap exists for New Zealand GP registrars' confidence to provide nutrition care, and their knowledge of evidence-based nutritional guidelines to support patients to have healthy dietary behaviours. A better understanding of the determinants of this disparity is required in order to support optimal nutrition care by GPs. Highlights: New Zealand general practitioner registrars do not demonstrate understanding of practice guidelines relating to nutrition. An evidence-practice gap exists with New Zealand general practitioner registrars. Understanding the determinants of this disparity is required.